A Case–Control Study of the Effects of Chronic Low Back Pain in Spatiotemporal Gait Parameters - Aurora Castro-Méndez; Inmaculada Requelo-Rodríguez; Manuel Pabón-Carrasco; María Luisa González-Elena; José Antonio Ponce-Blandón; Inmaculada Concepción Palomo-Toucedo (Sensors, 2021)
Chronic low back pain and biomechanical walking imbalances are closely related. It is relevant to identify if there are alterations in spatiotemporal gait patterns in subjects with CLBP (cases) versus healthy subjects (controls) to plan training interventions of motor control gait patterns, and thus allowing normal physical activity of the individual. This study is intended to identify if spatiotemporal alterations occur in the gait cycle in CLBP subjects (cases) compared with a control group (healthy patients) analyzed with an OptoGait LED sensors gait program. Method: A total of n = 147 participants: n = 75 cases (CLBP) and n = 72 healthy controls subjects were studied with OptoGait gait program. Results: Significant differences were found between the two groups and both feet in foot stride, for the differences of the total stride and contact, for gait cadence and total stride length of the gait cycle (p < 0.05). Conclusions: CLBP may alter some normal gait patterns measured by OptoGait; this finding presents imbalances in gait cycle as an underlying factor. The gait is part of daily life of any individual and it is an important physical activity in relation to the maintenance of an optimal state of health. In addition, future studies are deemed necessary.